Drug-loaded stainless steel stent and preparation process thereof
Patent Information
- Application Number
- CN202411502074.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-25
AI Technical Summary
After being implanted into the human body, stainless steel stents are easily a place for bacteria to adhere and proliferate, leading to infection and complications. The adhesion performance of the drug coating is insufficient, which may trigger an intravascular inflammatory reaction or thrombosis.
By preparing the coating on the surface of the stainless steel bracket, using materials such as unsaturated monomers, modified hydroxyapatite and chitosan, combined with ultraviolet light to induce polymerization and quaternization reactions, forming a composite coating with antibacterial and adhesion properties. .
It significantly improves the antibacterial properties and adhesion of stainless steel stents, reduces the risk of infection and the possibility of drug coating falling off, and enhances the biocompatibility and therapeutic effect of the stent.
Smart Images

Figure BDA0005102870870000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel, in particular to a drug-loaded stainless steel stent and a preparation process thereof. Background Art
[0002] Cardiovascular disease is one of the leading causes of death worldwide, so it is crucial to develop effective treatments. In this regard, the use of stainless steel stents provides patients with a better quality of life and survival rate. On the one hand, the use of stainless steel stents has significantly improved the prognosis of patients, allowing them to return to normal life and work. The timely implantation of stents can effectively restore blood flow, relieve angina symptoms, and reduce the risk of myocardial infarction. In addition, the use of stainless steel stents has also promoted the implementation of secondary prevention measures, allowing patients to better manage their lifestyle and drug therapy after surgery, thereby reducing the incidence of cardiovascular events. On the other hand, the advancement of stainless steel stent technology is also reflected in the combination with drug release systems. Many new drug-coated stents further reduce the risk of restenosis by releasing drugs on the surface of the stent. This drug coating not only improves the stent's anti-thrombotic properties, but also enhances the treatment effect, allowing patients' cardiovascular health to be effectively managed.
[0003] However, after stainless steel stents are implanted in the human body, they are prone to become places for bacteria to attach and proliferate due to the characteristics of their materials. The biofilms formed by these bacteria can lead to difficult-to-treat infections, and in severe cases may cause life-threatening complications such as sepsis. Therefore, there is an urgent need to improve the antibacterial properties of stents, so as to effectively inhibit the attachment of bacteria, reduce the probability of infection, and improve the patient's postoperative survival rate. In addition, the surface of the stent is usually coated with drugs or other functional materials to enhance its biocompatibility and therapeutic effect. If the adhesion of the coating is insufficient, the coating may fall off during or after stent implantation. The detached coating particles may induce intravascular inflammatory reactions or thrombosis, and in severe cases may lead to complications such as vascular restenosis or embolism. Therefore, improving the adhesion of the coating can effectively prevent the occurrence of these adverse events and ensure the safety of the stent.
[0004] In order to overcome the defects of the prior art, the present invention provides a drug-loaded stainless steel stent and a preparation process thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a drug-loaded stainless steel stent and a preparation process thereof to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A process for preparing a drug-loaded stainless steel stent comprises the following steps:
[0008] Step 1: The stainless steel stent is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then a benzophenone acetone solution is added, and polymerization is initiated by 360-365nm ultraviolet for 30-40min to obtain a pretreated stainless steel stent; the pretreated stainless steel stent is then immersed in a 1-bromooctane solution, and a quaternization reaction is carried out at 70-75°C for 20-24h. After the reaction is completed, the quaternized coating is obtained by washing and drying;
[0009] Step 2: dissolving thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; then immersing the stainless steel stent prepared in step 1 in the mixed solution, reacting under 360-365nm ultraviolet light for 15-20h, and washing with alcohol and vacuum drying after the reaction to obtain a composite coating;
[0010] Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 15-25 hours, and then rinsing with deionized water for 4-6 hours to obtain a finished product.
[0011] More optimally, in step 1, the unsaturated monomers include methacrylic acid, N,N-dimethylaminoethyl methacrylate, 2-methyl-2-acrylate-2-(2-methoxyethoxy)ethyl ester, and 3-methacryloyl dopamine, and the reaction molar ratio is 1:(3-4):2:(3-4); the amount of the modified hydroxyapatite is 8-10wt% of the total mass of the unsaturated monomers, and the benzophenone acetone solution is 20-25wt%.
[0012] More optimally, the preparation process of modified hydroxyapatite is: acrylic acid, p-toluenesulfonic acid, and hydroquinone are mixed, and then nano-hydroxyapatite is added and ultrasonically dispersed for 15-20 minutes, and then heated to condense and reflux for 2-4 hours. After the reaction is completed, the modified hydroxyapatite is obtained by filtration and drying.
[0013] More optimally, the contents of the components of the modified hydroxyapatite are: by mass fraction, 35-40% acrylic acid, 8-10% p-toluenesulfonic acid, 0.5-0.7% hydroquinone, and the remainder is nano-hydroxyapatite.
[0014] More optimally, in step 1, 1-bromooctane is dissolved in N,N-dimethylformamide to obtain a 1-bromooctane solution with a concentration of 10-15 g / ml.
[0015] More optimally, in step 2, the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is (90-95):1.
[0016] More optimally, the preparation process of thiolated chitosan is as follows: chitosan powder is added to a mixed solvent, stirred for 30-40 minutes, and then 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid are added, reacted in the dark for 12-15 hours, and after the reaction is completed, the thiolated chitosan is obtained by washing with water, washing with alcohol, and drying.
[0017] More optimally, the mixed solvent consists of acetonitrile and deionized water, and the mixing volume ratio is (1.5-2.0):1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:(0.7-0.8).
[0018] More optimally, in step three, the concentration of the drug solution is 20-30wt%.
[0019] Beneficial effects of the present invention:
[0020] The feature of the present invention is that in step one, a coating is prepared on the surface of a stainless steel stent by adding a benzophenone acetone solution, an unsaturated monomer, and modified hydroxyapatite to obtain a pretreated stainless steel stent. The coating prepared on the surface of the stainless steel stent substrate in this step can be evenly and stably covered on the surface of the substrate, thereby improving the wear resistance of the substrate. The unsaturated monomers include methacrylic acid, N,N-dimethylaminoethyl methacrylate, 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 3-methacryloyl dopamine; by adding 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, a flexible antifouling segment is introduced into the polymer, which can effectively improve the antifouling and antibacterial properties of the stainless steel stent surface; in this step, by adding 3-methacryloyl dopamine monomer, a dopamine fragment is introduced into the polymer, which can effectively improve the adhesion and mechanical stability of the stainless steel stent surface; by adding modified hydroxyapatite, a hydroxyapatite with good biocompatibility is introduced into the polymer, which can significantly enhance the adhesion strength of the coating, promote cell attachment and proliferation, and support bioremediation. Furthermore, in this step, the pretreated stainless steel stent is immersed in a 1-bromooctane solution for quaternization treatment to obtain a quaternary ammonium salt bactericidal chain segment, thereby effectively improving the antibacterial properties of the stainless steel stent surface.
[0021] The present invention is characterized in that, in step 2, thiolated chitosan is prepared by adding chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid; the stainless steel stent with the quaternized coating is immersed in a mixed solution of thiolated chitosan and a photoinitiator, and a composite coating is prepared by a thiol-ene click reaction. This step introduces chitosan with natural antibacterial properties into the surface coating, which can effectively inhibit the growth of bacteria and reduce the infection risk of the surface of the biomaterial; this chitosan can also promote the repair and regeneration of tissues, and has a positive effect on the healing of damaged tissues.
[0022] The present invention is characterized in that, in step three, the growth factor is dissolved in deionized water to obtain a liquid medicine; the stainless steel stent with the composite coating is immersed in the liquid medicine to obtain a finished product. In summary, the coating prepared on the surface of the stainless steel stent of the present invention has good antibacterial and adhesion properties, and therefore has broad application prospects in the field of stainless steel technology. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Source of raw materials:
[0025] The stainless steel stent is specifically 316L stainless steel; the growth factor is epidermal growth factor; the particle size of nano-hydroxyapatite is 200nm; and the chitosan powder specification is 100 mesh.
[0026] Example 1: Step 1: 40% acrylic acid, 10% p-toluenesulfonic acid, and 0.7% hydroquinone were mixed by mass fraction, and then 49.3% nano-hydroxyapatite was added and ultrasonically dispersed for 20 minutes, and then heated and condensed to reflux for 4 hours. After the reaction was completed, the modified hydroxyapatite was obtained by suction filtration and drying;
[0027] The stainless steel bracket is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then 25wt% of benzophenone acetone solution is added, and polymerization is initiated by 365nm ultraviolet for 40min to obtain a pretreated stainless steel bracket; the unsaturated monomer includes 1mol of methacrylic acid, 3.5mol of methacrylic acid-N,N-dimethylaminoethyl ester, 2mol of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 3.5mol of 3-methacryloyl dopamine, and 120ml of deionized water is used as a solvent; the amount of the modified hydroxyapatite is 10wt% of the total mass of the unsaturated monomer;
[0028] Then, the pretreated stainless steel stent was immersed in a 15 g / ml 1-bromooctane solution and subjected to a quaternization reaction at 75° C. for 24 h. After the reaction was completed, the quaternized coating was obtained by washing and drying.
[0029] Step 2: adding chitosan powder to a mixed solvent, stirring for 40 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid, reacting for 15 hours in the dark, washing with water, washing with alcohol, and drying after the reaction to obtain thiolated chitosan; the mixed solvent is composed of acetonitrile and deionized water, and the mixing volume ratio is 2:1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:0.8;
[0030] Dissolve thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; immerse the stainless steel stent prepared in step 1 in the mixed solution, and react under 365nm ultraviolet light for 20 hours. After the reaction is completed, wash with alcohol and vacuum dry to obtain a composite coating; the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is 95:1;
[0031] Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 25 hours, and then rinsing with deionized water for 6 hours to obtain a finished product; the concentration of the drug solution is 30wt%.
[0032] Example 2: Step 1: By mass fraction, 40% acrylic acid, 10% p-toluenesulfonic acid, and 0.7% hydroquinone were mixed, and then 49.3% nano-hydroxyapatite was added and ultrasonically dispersed for 17 minutes, and then heated to condense and reflux for 3 hours. After the reaction was completed, the modified hydroxyapatite was obtained by suction filtration and drying;
[0033] The stainless steel bracket is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then 25wt% of benzophenone acetone solution is added, and polymerization is initiated by 365nm ultraviolet for 35min to obtain a pretreated stainless steel bracket; the unsaturated monomer includes 1mol of methacrylic acid, 3.5mol of methacrylic acid-N,N-dimethylaminoethyl ester, 2mol of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 3.5mol of 3-methacryloyl dopamine, and 120ml of deionized water is used as a solvent; the amount of the modified hydroxyapatite is 10wt% of the total mass of the unsaturated monomer;
[0034] Then, the pretreated stainless steel stent was immersed in a 15 g / ml 1-bromooctane solution and subjected to a quaternization reaction at 73° C. for 22 h. After the reaction, the quaternized coating was obtained by washing and drying.
[0035] Step 2: adding chitosan powder to a mixed solvent, stirring for 35 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid, reacting for 13 hours in the dark, washing with water, washing with alcohol, and drying after the reaction to obtain thiolated chitosan; the mixed solvent is composed of acetonitrile and deionized water, and the mixing volume ratio is 2:1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:0.8;
[0036] Dissolve thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; immerse the stainless steel stent prepared in step 1 in the mixed solution, and react under 365nm ultraviolet light for 17 hours. After the reaction is completed, wash with alcohol and vacuum dry to obtain a composite coating; the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is 95:1;
[0037] Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 20 hours, and then rinsing with deionized water for 5 hours to obtain a finished product; the concentration of the drug solution is 30wt%.
[0038] Example 3: Step 1: By mass fraction, 40% acrylic acid, 10% p-toluenesulfonic acid, and 0.7% hydroquinone were mixed, and then 49.3% nano-hydroxyapatite was added and ultrasonically dispersed for 15 minutes, and then heated and condensed to reflux for 2 hours. After the reaction was completed, the modified hydroxyapatite was obtained by suction filtration and drying;
[0039] The stainless steel bracket is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then 25wt% of benzophenone acetone solution is added, and polymerization is initiated by 365nm ultraviolet for 30min to obtain a pretreated stainless steel bracket; the unsaturated monomer includes 1mol of methacrylic acid, 3.5mol of methacrylic acid-N,N-dimethylaminoethyl ester, 2mol of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, 3.5mol of 3-methacryloyl dopamine, and 120ml of deionized water is used as a solvent; the amount of the modified hydroxyapatite is 10wt% of the total mass of the unsaturated monomer;
[0040] Then, the pretreated stainless steel stent was immersed in a 15 g / ml 1-bromooctane solution, and a quaternization reaction was carried out at 70° C. for 20 h. After the reaction was completed, the quaternized coating was obtained by washing and drying.
[0041] Step 2: adding chitosan powder to a mixed solvent, stirring for 30 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid, reacting for 12 hours in the dark, washing with water, washing with alcohol, and drying after the reaction to obtain thiolated chitosan; the mixed solvent is composed of acetonitrile and deionized water, and the mixing volume ratio is 2:1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:0.8;
[0042] Dissolve thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; then immerse the stainless steel stent prepared in step 1 in the mixed solution, and react under 365nm ultraviolet light for 15 hours. After the reaction is completed, wash with alcohol and vacuum dry to obtain a composite coating; the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is 95:1;
[0043] Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 15 hours, and then rinsing with deionized water for 4 hours to obtain a finished product; the concentration of the drug solution is 30wt%.
[0044] Comparative Example 1: The reaction molar ratio of methacrylic acid, methacrylic acid-N,N-dimethylaminoethyl ester, 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 3-methacryloyl dopamine is changed to 1:1:2:1, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: In terms of mass fraction, 40% acrylic acid, 10% p-toluenesulfonic acid, and 0.7% hydroquinone are mixed, and then 49.3% nano-hydroxyapatite is added and ultrasonically dispersed for 20 minutes, and then heated to condense and reflux for reaction for 4 hours. After the reaction is completed, it is filtered and dried to obtain modified hydroxyapatite;
[0045] The stainless steel bracket is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then 25wt% of benzophenone acetone solution is added, and polymerization is initiated by 365nm ultraviolet for 40min to obtain a pretreated stainless steel bracket; the unsaturated monomer includes 1mol of methacrylic acid, 1mol of methacrylic acid-N,N-dimethylaminoethyl ester, 2mol of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 1mol of 3-methacryloyl dopamine, and 120ml of deionized water is used as a solvent; the amount of the modified hydroxyapatite is 10wt% of the total mass of the unsaturated monomer;
[0046] Then, the pretreated stainless steel stent was immersed in a 15 g / ml 1-bromooctane solution and subjected to a quaternization reaction at 75° C. for 24 h. After the reaction was completed, the quaternized coating was obtained by washing and drying.
[0047] Step 2: adding chitosan powder to a mixed solvent, stirring for 40 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid, reacting for 15 hours in the dark, washing with water, washing with alcohol, and drying after the reaction to obtain thiolated chitosan; the mixed solvent is composed of acetonitrile and deionized water, and the mixing volume ratio is 2:1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:0.8;
[0048] Dissolve thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; immerse the stainless steel stent prepared in step 1 in the mixed solution, and react under 365nm ultraviolet light for 20 hours. After the reaction is completed, wash with alcohol and vacuum dry to obtain a composite coating; the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is 95:1;
[0049] Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 25 hours, and then rinsing with deionized water for 6 hours to obtain a finished product; the concentration of the drug solution is 30wt%.
[0050] Comparative Example 2: The modified hydroxyapatite is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The stainless steel bracket is washed with water, alcohol, and acid, and then taken out and immersed in an unsaturated monomer, and then a 25wt% benzophenone acetone solution is added, and the polymerization is initiated by 365nm ultraviolet for 40min to obtain a pretreated stainless steel bracket; the unsaturated monomer includes 1mol of methacrylic acid, 1mol of methacrylic acid-N,N-dimethylaminoethyl ester, 2mol of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 1mol of 3-methacryloyl dopamine, and 120ml of deionized water is used as a solvent;
[0051] Then, the pretreated stainless steel stent was immersed in a 15 g / ml 1-bromooctane solution and subjected to a quaternization reaction at 75° C. for 24 h. After the reaction was completed, the quaternized coating was obtained by washing and drying.
[0052] Step 2: adding chitosan powder to a mixed solvent, stirring for 40 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid, reacting for 15 hours in the dark, washing with water, washing with alcohol, and drying after the reaction to obtain thiolated chitosan; the mixed solvent is composed of acetonitrile and deionized water, and the mixing volume ratio is 2:1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:0.8;
[0053] Dissolve thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; immerse the stainless steel stent prepared in step 1 in the mixed solution, and react under 365nm ultraviolet light for 20 hours. After the reaction is completed, wash with alcohol and vacuum dry to obtain a composite coating; the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is 95:1;
[0054] Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 25 hours, and then rinsing with deionized water for 6 hours to obtain a finished product; the concentration of the drug solution is 30wt%.
[0055] Comparative Example 3: excluding step 2, the rest is the same as Example 1, and the specific steps are as follows: Step 1: by mass fraction, 40% acrylic acid, 10% p-toluenesulfonic acid, and 0.7% hydroquinone are mixed, and then 49.3% nano-hydroxyapatite is added and ultrasonically dispersed for 20 minutes, and then heated to condense and reflux for 4 hours. After the reaction is completed, the modified hydroxyapatite is obtained by suction filtration and drying;
[0056] The stainless steel bracket is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then 25wt% of benzophenone acetone solution is added, and polymerization is initiated by 365nm ultraviolet for 40min to obtain a pretreated stainless steel bracket; the unsaturated monomer includes 1mol of methacrylic acid, 1mol of methacrylic acid-N,N-dimethylaminoethyl ester, 2mol of 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 1mol of 3-methacryloyl dopamine, and 120ml of deionized water is used as a solvent; the amount of the modified hydroxyapatite is 10wt% of the total mass of the unsaturated monomer;
[0057] Then, the pretreated stainless steel stent was immersed in a 15 g / ml 1-bromooctane solution and subjected to a quaternization reaction at 75° C. for 24 h. After the reaction was completed, the quaternized coating was obtained by washing and drying.
[0058] Step 2: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent with the quaternized ammonium coating in the drug solution for 25 hours, and then rinsing with deionized water for 6 hours to obtain a finished product; the concentration of the drug solution is 30wt%.
[0059] Detection test:
[0060] Antibacterial performance test: The coating on the surface of the finished stainless steel stent prepared by the present invention was evenly scraped, and the scraped product was added with phosphate buffer to prepare a 3 μg / mL solution, and then 10 mL of the inoculated Staphylococcus aureus solution was added, and the mixture was cultured at 28°C for 3 h. The solution was diluted and inoculated into the culture medium, and cultured at 28°C for 20 h. The number of colony growth was observed and recorded, and the antibacterial rate was calculated.
[0061] Cell activity test: The coating on the surface of the finished stainless steel stent prepared by the present invention is evenly scraped, and the scraped product is added to the DMED culture medium and soaked for 48 hours to obtain a standby sample solution. L-929 fibroblasts are cultured under a constant temperature of 5% CO2 and 37°C. The cells are added to the sample solution, cultured for 4 days, and then the MTT detection reagent is added and cultured for 4 hours at 37°C in the dark, and then sodium dodecyl sulfate is added and mixed evenly, and finally the cell activity is calculated by testing the absorbance of the sample solution.
[0062] Adhesion performance test: In the preparation process of the present invention, 1wt% of aniline blue dye is added to the unsaturated monomer to prepare a pretreated stainless steel bracket, which is then quaternized to obtain a stainless steel bracket with a quaternized coating as a sample. The tape is fully adhered to the surface of the sample, and the degree of coating peeling on the surface of the sample is recorded by taking pictures. The results are as follows:
[0063]
[0064] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that there is no obvious fluctuation in the performance of the samples.
[0065] Comparative Example 1: The reaction molar ratio of methacrylic acid, N,N-dimethylaminoethyl methacrylate, 2-methyl-2-acrylic acid-2-(2-methoxyethoxy)ethyl ester, and 3-methacryloyl dopamine was changed to 1:1:2:1, and the rest was the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate was changed to 94.6%, the cell activity was changed to 83%, and the degree of coating peeling was that small fragments or particles peeled off on the surface. The reason was analyzed as follows: when preparing the quaternary ammonium coating, the present invention prepared a coating with good antibacterial and adhesion properties by setting the preferred reaction molar ratio. Therefore, after the reaction molar ratio was changed to 1:1:2:1, the antibacterial chain breaks and adhesion chain breaks were reduced, so the antibacterial rate was reduced, the cell activity was reduced, and the degree of coating peeling was increased.
[0066] Comparative Example 2: The modified hydroxyapatite was removed, and the rest was the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the cell activity became 85%, and the degree of coating peeling was more obvious in some areas. The reason for this was analyzed as follows: hydroxyapatite can significantly enhance the adhesion strength of the coating, promote cell attachment and proliferation, so after the modified hydroxyapatite was removed, the cell activity decreased and the degree of coating peeling increased.
[0067] Comparative Example 3: Step 2 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate becomes 90.8%, and the cell activity becomes 81%. The reason is analyzed as follows: the present invention introduces chitosan with natural antibacterial properties on the surface of the stainless steel stent with a hydrogel carrier coating, which can effectively inhibit the growth of bacteria, reduce the risk of infection on the surface of the biomaterial, and enhance cell activity. Therefore, after removing step 2, the antibacterial rate is reduced and the cell activity is reduced.
[0068] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0069] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a drug-loaded stainless steel stent, characterized in that: The following steps are involved: Step 1: The stainless steel stent is washed with water, alcohol and acid, taken out and immersed in an unsaturated monomer, modified hydroxyapatite is added, and then a benzophenone acetone solution is added, and polymerization is initiated by 360-365nm ultraviolet for 30-40min to obtain a pretreated stainless steel stent; the pretreated stainless steel stent is then immersed in a 1-bromooctane solution, and a quaternization reaction is carried out at 70-75°C for 20-24h. After the reaction is completed, the quaternized coating is obtained by washing and drying; Step 2: dissolving thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone in toluene to obtain a mixed solution; then immersing the stainless steel stent prepared in step 1 in the mixed solution, reacting under 360-365nm ultraviolet light for 15-20h, and washing with alcohol and vacuum drying after the reaction to obtain a composite coating; Step 3: dissolving the growth factor in deionized water to obtain a drug solution; immersing the stainless steel stent obtained in step 2 in the drug solution for 15-25 hours, and then rinsing with deionized water for 4-6 hours to obtain a finished product.
2. The process for preparing a drug-loaded stainless steel stent according to claim 1, characterized in that: In step 1, the unsaturated monomers include methacrylic acid, N,N-dimethylaminoethyl methacrylate, 2-methyl-2-acrylate-2-(2-methoxyethoxy)ethyl ester, and 3-methacryloyl dopamine, and the reaction molar ratio is 1:(3-4):2:(3-4); the amount of the modified hydroxyapatite is 8-10wt% of the total mass of the unsaturated monomers, and the benzophenone acetone solution is 20-25wt%.
3. The process for preparing a drug-loaded stainless steel stent according to claim 2, characterized in that: The preparation process of modified hydroxyapatite is as follows: acrylic acid, p-toluenesulfonic acid and hydroquinone are mixed, nano-hydroxyapatite is added and ultrasonically dispersed for 15-20 minutes, and then heated, condensed and refluxed for 2-4 hours. After the reaction is completed, the modified hydroxyapatite is obtained by filtration and drying.
4. The process for preparing a drug-loaded stainless steel stent according to claim 3, characterized in that: The contents of each component of the modified hydroxyapatite are as follows: by mass fraction, 35-40% acrylic acid, 8-10% p-toluenesulfonic acid, 0.5-0.7% hydroquinone, and the balance is nano-hydroxyapatite.
5. The process for preparing a drug-loaded stainless steel stent according to claim 1, characterized in that: In step 1, 1-bromooctane is dissolved in N,N-dimethylformamide to obtain a 1-bromooctane solution with a concentration of 10-15 g / ml.
6. The process for preparing a drug-loaded stainless steel stent according to claim 1, characterized in that: In step 2, the reaction mass ratio of thiolated chitosan and photoinitiator 2,2-dimethoxy-2-phenylacetophenone is (90-95):
1.
7. The process for preparing a drug-loaded stainless steel stent according to claim 6, characterized in that: The preparation process of thiolated chitosan is as follows: chitosan powder is added to a mixed solvent, stirred for 30-40 minutes, and then 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid are added, reacted in the dark for 12-15 hours, and after the reaction is completed, the thiolated chitosan is obtained by washing with water, washing with alcohol, and drying.
8. The process for preparing a drug-loaded stainless steel stent according to claim 7, characterized in that: The mixed solvent consists of acetonitrile and deionized water, and the mixing volume ratio is (1.5-2.0):1; the reaction mass ratio of chitosan powder, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and mercaptopropionic acid is 1:1:(0.7-0.8).
9. The process for preparing a drug-loaded stainless steel stent according to claim 1, characterized in that: In step three, the concentration of the drug solution is 20-30wt%.
10. A drug-loaded stainless steel stent, characterized in that: Prepared according to the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Medical antibacterial material as well as preparation method and application thereof
CN115340698A
Medical catheter surface lubricating antibacterial drug-loaded coating as well as preparation method and application thereof
CN117442787A
Complex and production method for complex
WO2021049515A1